Electronic Structure of Phosphorous Doped Bulk Silicon and Its Use for Spin Qubits for Quantum Computation (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied the electronic structure of silicon dopants which is necessary for  implementation of spin based qubits in silicon. Description of dopant in silicon is  therefore useful both as a benchmark and for determining the details of the  electronic structure of an isolated dopant which can subsequently be used to  calculate more accurate spin dependent scattering cross sections. These calculation  have been able to perform large scale calculations using the computational  resources. We have performed two electron Hartree-Fock calculations within  effective mass theory. These efforts include calculating the effects of applied electric  and magnetic fields and the coupling of two donors via exchange interaction. Tight  binding calculations have also been performed including a calculation of the  quadratic stark coefficient of the hyper interaction. We have found an  unprecedented level of structure in the doping potentials and densities and wave  functions. Due to oscillatory nature of doping potentials, the exchange coupling  between qubits obtained by extrapolating our results to smaller distances was found  to be less than estimates based on the Heitler-London approximation. The obtained  results were found in good agreement with previously obtained results.